2021
DOI: 10.1039/d1dt00719j
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced γ-phase crystallinity of Al2O3 frameworks at the concave surface of PS-b-PEO templated spherical pores

Abstract: Crystallinity of inorganic solids like metal oxides after the porosity design is the crucial factor that should be investigated for enhancing their physicochemical property. In most cases, metal oxide frameworks...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 50 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…3). 50,51 Considering such an expansion of surfactant-assisted mesopores, a tendency to decrease the specific surface area (from 103 m 2 g −1 to 63 m 2 g −1 ) but with an increase in total pore volume (from 0.26 cm 3 g −1 to 0.40 cm 3 g −1 ) is quite reasonable. 52,53 A mesoporous TiO 2 powder sample was additionally prepared using a different kind of PS- b -PEO (PS < PEO, PS/PEO = 0.46) like PS 18000 - b -PEO 39000 .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…3). 50,51 Considering such an expansion of surfactant-assisted mesopores, a tendency to decrease the specific surface area (from 103 m 2 g −1 to 63 m 2 g −1 ) but with an increase in total pore volume (from 0.26 cm 3 g −1 to 0.40 cm 3 g −1 ) is quite reasonable. 52,53 A mesoporous TiO 2 powder sample was additionally prepared using a different kind of PS- b -PEO (PS < PEO, PS/PEO = 0.46) like PS 18000 - b -PEO 39000 .…”
Section: Resultsmentioning
confidence: 92%
“…Our previous study on the aerosol-assisted synthesis of mesoporous alumina (Al 2 O 3 ) powders using PS-b-PEO revealed the importance of the PS/PEO ratio in changing the pore size. 26,51 In this context, several PS-b-PEO type asymmetric diblock copolymers with similar molecular structure (PS > PEO, with the PS/PEO value ranging from 1.8 to 2.4) were utilized to control the mesopore size. All the other samples were fully crystallized as the anatase phase of titania (see Fig.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…The mesoporous structure of the catalyst would benet the enhancement of the catalytic performance due to its high surface area, large pore volume and tunable pore size related to the diffusivity as well as mass transport properties. [31][32][33][34] The spray-drying process is capable of designing the morphology of resultant materials (typically spherical), 9,[35][36][37][38][39][40][41][42][43] which is sometimes helpful for improving the catalytic performance. 44,45 The BaO/Pt@mTiO 2 type catalyst was characterized and utilized for investigating the catalytic performance during the gas-switching NO x storage reduction (NSR) process that involves sequential reactions, such as the oxidation of NO, the storage of NO 2 and the reduction of solidstate NO 3 − species for the synthesis of NH 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The morphology seemed different from that observed for mesoporous metal oxide particles, which were typically aggregated as spherical ones, prepared by an aerosol-assisted synthesis using amphiphilic organic molecules. 14–16,27 This was likely be due to the strongly ethanolic synthesis without water showing a high surface tension. The TEM images revealed that the PS- b -PEO-templated mesopores were surrounded by fine CeO 2 nanoparticles (around 3 nm) (see (a) and (b) in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…According to this realistic approach, we can save much of the working time for optimizing chemical composition, which has already been demonstrated through the synthesis of porous Al 2 O 3 powders using poly(styrene)- block -poly(ethylene oxide) (PS- b -PEO). 14–16…”
Section: Introductionmentioning
confidence: 99%